Legal Education in Indonesia - Bedner, Adriaan; Vel, Jacqueline (UI Scholars Hub, 2021)
Many of the discussions about legal education in Indonesia are similar to the ones conducted in other countries. They reflect the tension between a liberal legal education on the one hand and a vocational training on the other, as well as the tension between a legal education preparing students for legal practice and one preparing them for a broad range of generalist positions. However, we argue that legal education in Indonesia is also marred by problems of the legal system itself and by a lack of communication between its constituent parts – the judiciary, the legislative, the bar, public prosecutors, and legal scholars. Caused by years of authoritarian rule, these problems have resulted in an unproductive and largely misguided debate in law faculties between proponents of legal formalism and others promoting a more contextualised approach to law. Nonetheless, it is undeniable that overall the quality of legal education has improved during the past 20 years and that this process will likely continue.